Do learning ICT usage affect the learning process quality? an empirical study in private university - Nindhita, Yoga; Budiyanto, Budiyanto; Djarwoto, Djarwoto (Technium Social Sciences Journal, 2022)
Information Communication Technology (ICT) brings new opportunities to many aspects of society. Applying ICT in education is a valuable contribution to improving quality, especially improving the quality of the learning process in higher education. This study explains the relationship between research variables by testing the description hypothesis. Variables include Learning process quality, ICT learning usage, Technology Characteristics, Individual Characteristics, and Motivation to use ICT. The Structural Equation Modeling (SEM) was used to analyze the data in this study. The results show a significant positive effect of learning usage ICT variables, Technology Characteristics, and Individual Characteristics on the quality of the learning process, then Individual Characteristics and Motivation use ICT on ICT learning usage. Meanwhile, the Technology Characteristic variable has no significant positive effect on ICT learning usage. The influence of significant positive variables is expected to be able to be utilized and managed properly so that, in the future, a high-quality learning process will be achieved. Campuses can also act as a forum by providing various competency training so that teaching staff becomes more prepared and competent in learning using ICT. Furthermore, the provision of learning using ICT can be better optimized so that the potential characteristics of the technology can be utilized to the fullest.